"Electric Word Life": Methodological Dignity in Equity-Driven Research. Issue 3 (2nd July 2020) - Garcia, Antero
ABSTRACT: In this essay, I offer methodological considerations for justice-oriented qualitative research. Particularly within the context of Trumpism within the U.S. and rising threats to historically marginalized communities globally, this essay explores how research for equity-driven scholarship must attend to frequently invisible sociopolitical learning. Specifically, I illustrate how three elements of research—often taken up separately—comprise elements researchers must consider in our work. I frame these overlapping layers as part of a framework for methodological dignity. First, platforms, as non-neutral factors shaping where and how research is undertaken, are examined within the contexts of learning and schooling. Next, I look at how the communities and environments in which research is conducted both impact and are impacted by research processes. Finally, although research positionality is commonly covered in scholarly manuscripts, I explore how this shifting aspect of scholarship impacts the kinds of questions asked and how they are studied.